Effect of different shielding conditions on the stability of Cisplatin - Tomoya Abe; Daigo Matsumoto; Toshiaki Nakayama; Yukinari Shimazaki; Atsunobu Sagara; Dan Kanehira; Takuya Azechi; Fumiaki Sato; Hiroyasu Sakai; Tetsuro Yumoto; Junzo Kamei (BMC, 2020)
Abstract Background Because cisplatin (CDDP) decreases upon light exposure, it is necessary to prevent such exposure during administration. However, the shielding conditions employed are not uniform. Therefore, in this study, we examined the shielding effects of four shading covers, which are commonly used to ensure the stability of CDDP in clinical settings. Methods Four shielding conditions, along with a control, were tested under a 1000-Lux white fluorescent lamp at room temperature: aluminum foil (Al), brown shading cover (BSC), yellow shading cover (YSC), milky-white anti-exposure cover (MAC), and no shading cover (NSC). Under each shielding condition, the relationship between the wavelength and transmittance was monitored in the range of 200-800 nm. CDDP was diluted to three concentration levels: 50, 100, and 250 μg/mL. Furthermore, the amount of remaining CDDP and the pH in the solutions were measured for 120 h. Results We found that BSC, YSC, and MAC conditions allowed various levels of transmittance; however, Al could not completely transmit light at all wavelengths. Moreover, we showed that the CDDP decreased under MAC and NSC conditions in a time-dependent manner, whereas this decrease was prevented under Al, BSC, and YSC conditions till 120 h. We also demonstrated increases in pH under MAC and NSC conditions in a time-dependent manner, which was prevented under Al, BSC, and YSC conditions till 120 h. Similar results were observed for all three CDDP concentration levels. The results also indicated the approximate relationship between the amount of remaining CDDP and the pH increase. Conclusions Considering the opacity of each cover, our results suggest that BSC and YSC are useful and effective for minimizing CDDP degradation in clinical settings. Our results also indicate the alternatives for preparing, storing, and administering CDDP in clinical facilities, making the treatment schedule more flexible. Cumulatively, these findings indicate that the use of the appropriate shading covers, such as BSC or YSC, prevents the decrease in CDDP under fluorescent lighting, potentially contributing to achieving its full therapeutic effect.